Cloud Computing: Current and Future - Taqwan Thamrin; Marzuki Marzuki; Reni Nursyanti; Andala Rama Putra (Bandar Lampung University (UBL), 2012)
Cloud computing are distributed processing, parallel processing and the development of grid computing, the concept was jointly proposed by Google and IBM in 2007. Cloud computing refers to a network that distributes processing power, applications, and large systems among many computers. Social media channels and many other applications use cloud computing as their platform. Cloud computing, the aim is to hide the complexity of IT infrastructure management from its users. At the same time, cloud computing platforms provide massive scalability, 99.999% reliability, high performance, and specifiable configurability. These capabilities are provided at relatively low costs compared to dedicated infrastructures. Cloud computing is a complex infrastructure of software, hardware, processing, and storage that is available as a service. This paper discuss regarding the study of the basic concepts of cloud computing technology, core technology, several different types of clouds services, target dimensionand challenges of cloud computing in current and future.